The Effect of Rewards, Punishment and Work Discipline on Operational Employee Performance at J&T Express Bandung Greater Operational Area - Gilang Atriyanto Putra; Nina Nurani (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
Technological developments in the digital era have transformed consumer purchasing behavior. People are now increasingly savvy in utilizing technological advancements, requiring companies to maintain and improve employee performance to keep pace with these changes. Employee performance is a crucial factor for business sustainability, as human resources, or human capital, are a company's primary asset. Employees play a key role in achieving the organization's vision and mission. However, some companies still fail to recognize the strategic value of employees as an asset. The purpose of this study is to analyze the influence of rewards, punishments, and work discipline on the performance of J&T Express employees in the Greater Bandung Operational Area. The research method is quantitative associative, the sampling technique used in this study is non-probability sampling, the data analysis test of this research uses Multiple Linear Regression analysis, Determination Coefficient, Goodness Fit Model Test (F Test), Individual Significance Test (t-Statistic Test), The results of the research show that  Rewards, Punishment, and Work Discipline Influence have a significant effect on the Performance of  J&T Express Operational Employees in the Greater Bandung Operational Area.